Konkurenčna politika v socialnem tržnem gospodarstvu - Ferčič, Aleš (Podjetje in delo, 2015)
The author discusses the very foundations of contemporary competition policy in the social market economy within the legal framework as defined by the European Union law. For this reason, he defines the concept of competition policy and its relationship to competition law; he discusses its position within the classical system ofvarious puhlic policies, its role and limits, and desired ways of its enforcement in a daily practice. Furthermore, the author discusses three selected questions related to the competition policy in the social market economy. The first question is related to the regulatory activities in infrastructure sectors with the special emphasis on the role and organization of independent regulatory bodies. Second question is related to the business activities according to the new paradigm in the liberalized sectors or better to say, in the sectors subject to the liberalization process, with the special emphasis on a good governance of public undertakings and on ultimate risks attached to their privatization, such as the use of golden shares or of unusual terms far the buyers in privatization transactions. And the third, also important question is related to the reorganization of certain public activities, i.e.from a non-market to market system. The author concludes by offering a set of theses applicable to performing competition policy in the social market economy.
Keywords: European Union; Evropska unija; gospodarsko pravo; konkurenca; konkurenčna politika; liberalizacija; regulacija; tržno gospodarstvo